Urgensi Teknologi E-Commerce Terhadap Pengembangan Usaha Mikro Kecil Menengah - Karsono, Lorena Dara Putri; Azzarqo, Khotiibah (Universitas Methodist Indonesia, 2024)
The Community Creativity Program is a program of student creativity activities involving lecturers and students. Community service activities collaboration between lecturers and students is a form of implementation of the Tridharma of Higher Education to the local community which is carried out by both lecturers and students. This activity is expected to increase independence, teamwork, and a sense of empathy, team solidarity and make a positive contribution in the future. The purpose of this activity is more directed at increasing the community's understanding of the potential of the village based on religious moderation, both economic, sociocultural and religious potential and also to develop the potential of students according to their scientific fields (producers) towards increasing their abilities and profession. One of the community service activities that collaborates with lecturers is an entrepreneurship seminar activity by holding a seminar on entrepreneurship which discusses marketing strategies in doing business which will later be useful for SMEs in the local community. This seminar activity aims to increase understanding of the importance of marketing strategies that compete with the 5.0 era. The introduction of e-commerce is also emphasized in this activity, therefore, as a business owner, you are required to learn more about marketing 5.0. This innovation in terms of marketing will have a direct effect on SMEs businesses that are being run or being initiated by business owners, and can also increase sales of SMEs in Sumanding village so that in the future sales will be even better according to the correct rules.